The Effectiveness of The Hello, Me! Program to Increase Teengaers’ Self-Awareness - Ulya, Laila Listiana; Stanislaus, Sugiyarta; Amawidyati, Sukma Galuh Adi; Mahanani, Fatma Kusuma; Arinata, Firdian Setiya (Edukasi, 2021)
During the Covid-19 pandemic, unemployment increased to 9.77 million. Youth competition in the world of work will be more challenging if they do not have soft and hard skills. Teenagers who grow up in an environment with complex social problems such as Tikungbaru, where poverty, crime, and juvenile delinquency rates are high, actually need it. Teenagers need self-awareness to select the right career. The purpose of the research was to determine the "Hello, Me!" by searching for interests and talents to increase teenagers' self-awareness. The research method uses an experimental pre-post test design with teenagers aged 12-13 years in RW 08 Tikungbaru. The intervention is the "Hello, Me!" program in tracking interests and talents through CFIT and RMIB, self-awareness training, and group counselling. The data collection uses a self-awareness scale before and after the program. Data analysis used the Parametric Paired-Samples T-test. The results show that sig (2-tailed) value of 0.000 0.05 means a significant difference in self-awareness in teenagers before and after the program. The conclusion is that "Hello, Me!" can increase teenagers' self-awareness in Tikungbaru. This research can provide literature references and program solutions to increase teenagers' self-awareness.